2022
DOI: 10.1021/acs.jpcc.2c03780
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Halogen and Sulfur Mixing on Lithium-Ion Conductivity in Li7–xy(PS4)(S2–xyClxBry) Argyrodite and the Mechanism for Enhanced Lithium Conduction

Abstract: All-solid-state lithium-ion batteries containing phosphorus sulfides are promising next-generation batteries because they have higher energy densities than their liquid-electrolyte counterparts. Halogen-rich argyrodites, Li7−α(PS4)­(S2−αXα) (X = Cl, Br, I; α > 1), exhibit higher ionic conductivities than other phosphorus sulfides; varying the content of a single anion enables halogen substitution. However, there is no appropriate model for the ion-conducting path in these argyrodites. Herein, we discuss a rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…However, recent reports have indicated that Li + can partially occupy the T4 site (Wyckoff 16 e , Figure b) in Li 6.15 Al 0.15 Si 1.35 S 5.4 O 0.6 and related Li 2 S-SnS 2 –SiS 2 –P 2 S 5 sulfides . Additionally, other argyrodites showed the Li + occupancy of T2 and T4 sites in “Li-deficient” materials with stoichiometries of <6.0 Li per formula unit . In order to study the lithium substructure in the Li 6– x PS 5– x Br 1+ x series, we conducted a detailed investigation using neutron powder diffraction, analyzed by Rietveld refinement in the cubic F 4̅3 m space group.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…However, recent reports have indicated that Li + can partially occupy the T4 site (Wyckoff 16 e , Figure b) in Li 6.15 Al 0.15 Si 1.35 S 5.4 O 0.6 and related Li 2 S-SnS 2 –SiS 2 –P 2 S 5 sulfides . Additionally, other argyrodites showed the Li + occupancy of T2 and T4 sites in “Li-deficient” materials with stoichiometries of <6.0 Li per formula unit . In order to study the lithium substructure in the Li 6– x PS 5– x Br 1+ x series, we conducted a detailed investigation using neutron powder diffraction, analyzed by Rietveld refinement in the cubic F 4̅3 m space group.…”
Section: Resultsmentioning
confidence: 97%
“…More charge is maintained on the Li atom as its electrons experience less interaction with the 4 d site, causing the 6 Li shift to move to lower ppm values . The increased Li cage radius is the origin of the reduced T2–T2 and T5–T4–T5 distances, effectively the result of the Br distribution over the 4 a and 4 d sites, which can be expected to result in better cage connectivity and thus higher overall conductivity. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While these reports 20,22,24 highlight the function of the 48h′ site (type 2) and support the idea 4 that the cage-tocage Li + jump may be achieved by the 48h−48h′−48h′−48h migration pathway (type 5−type 2−type 2−type 5, Figure 2), relatively little is known about the potential contribution of the interstitial 16e sites (type 4) to the Li + migration (Figures 1 and 2), despite some very recent bond valence sum (BVS) analysis on this site. 25 Pioneering works, experimentally 10,17 and computationally, 22,26 proposed that the fast Li + conduction in Li-argyrodite is strongly correlated with the degree of anion site-disorder, i.e., mixing of S 2− and Cl − /Br − /I − on the Wyckoff site of 4a/ 4d. It is broadly believed that high degrees of anion sitedisorder can facilitate fast Li + migration 27 by altering the energy landscape for different Li + sites.…”
Section: ■ Introductionmentioning
confidence: 99%